Molecular basis of heat stress tolerance in wheat - Preeti Kayastha; Barsha KC; Biddhya Pandey; Bimal Roka Magar; Himani Chand; Janak Bhandari; Pawan Lamichhane; Prakash Baduwal; Mukti Ram Poudel (Journal of Agriculture and Applied Biology, 2023)
The rise in Earth’s temperature is one of the most alarming climatic issues in the field of agriculture and food production, in the present context. The increase in temperature leads to heat stress, major abiotic stress responsible for a huge decline in the production of crops. Wheat (Triticum aestivum), among many crops, also experiences a significant decline in yield and overall productivity due to extreme heat stress. But Wheat has also developed natural tolerance mechanisms to defend itself from heat damage. The selection of cultivars with a higher degree of tolerance mechanism protects against thermal stress, which minimizes the risk of poor productivity to a greater extent. In this review, we discuss the current works of literature concerning the heat stress tolerance mechanism in wheat plants and also highlight the strategic approaches that improve their heat stress tolerance at the molecular level. The success of these approaches depends on a better understanding of heat tolerance traits, their genomic composition, and molecular responses.